Molecular Pathogenesis and Treatment Strategies of Chronic Myeloid Leukemia (CML) - Rabia Khalid; Sana Riasat (Sudan Journal of Medical Sciences, 2023)
Abstract Chronic Myeloid Leukemia (CML) is a myeloproliferative disease diagnosed in bone marrow, arising from a chromosomal translocation between chromosomes 9 and 22, resulting in the formation of fusion oncogene BCR–ABL. The product of this fusion oncogene is a new oncoprotein bcr–abl which possesses abnormal tyrosine kinase activity. In response to this, abnormal signaling pathway activation occurs, leading to cell transformation. BCR–ABL oncogene could be targeted by tyrosine kinase inhibitors (TKIs) to delay or inhibit the disease progression. Imatinib is the first drug designed against CML but resistance to this has led to the development of the second- and third generations of inhibitors that are active against many types of BCR–ABL gene mutations. However, somehow, due to disease progression, TKIs do not remain as effective. There are three well-characterized phases of CML: The chronic phase (CP), the accelerated phase, and the terminal stage which is the blast crisis (BC) stage. In the CP of CML, mature granulocytes and myeloid precursors become aggregated majorly in the bone marrow and peripheral blood. The accelerated phase is marked by increased disease severity and an increase in progenitor/precursor cell number. In the BC stage, undifferentiated blast cells grow in number. Many patients with CML are diagnosed during the CP of disease, so the survival rate of CML is high. However, 20% of CML patients proceed to advanced stages that result in drug resistance, intolerance, and mortality. So, for proper CML treatment, drugs are needed to target multiple BCR–ABL mutations, delay or stop disease progression, and overcome resistance caused by BCR–ABL independent mechanisms, especially during advanced phases of CML. Moreover, drugs could be developed to eradicate the stem cells of CML. These targets could be achieved by understanding mechanisms of disease progression, disease relapse, and drug resistance by utilizing high throughput molecular genetics, cell biology and immunology techniques.